Vertical distribution of earthworms in grassland soils of the Colombian "Llanos" - Jiménez Jaén, J.J.; Decaëns, Thibaud (International Center for Tropical Agriculture, 2001)
The vertical distribution of native earthworm species from natural and disturbed savannas in the Oxisols of the Colombian Llanos was assessed in a native savanna and in a 17-year-old grazed grass-legume pasture during a period of 17 months. Different patterns of vertical stratification were `Observed for all species with a strong migration of populations to deeper layers in the dry season. The correlation between the size of the earthworms and the average depth at which they were found was not significant (P>0.05), despite the fact that bigger species are located deeper in the soil. The living habits and adaptive strategies of the smallest species, Ocnerodrilidae n. sp. found in both ecosystems studied was responsible for this pattern. This endogeic species is associated with organic pools generated by an anecic: species and further studies should assess the role of this species in ecosystem functioning. Mature worms of one anecic species were located deeper than immature ones in the soil (P<0.01). Soil moisture had an important effect on the vertical distribution of earthworms, although differences between immature and mature worms of the anecic: Martiodrilus carimaguensis are likely to be of biotic origin. New data on the biology and ecology of these neotropical species are shown.